Ultra-high Q one-dimensional hybrid PhC-SPP waveguide microcavity with large structure tolerance. Issue 12 (3rd July 2016) - Liu, Feng; Zhang, Lingxuan; Lu, Xiaoyuan; Wang, Weiqiang; Wang, Leiran; Wang, Guoxi; Zhang, Wenfu; Zhao, Wei
Abstract: A photonic crystal – surface plasmon-polaritons hybrid transverse magnetic mode waveguide based on a one-dimensional optical microcavity is designed to work in the communication band. A Gaussian field distribution in a stepping heterojunction taper is designed by band engineering, and a silica layer compresses the mode field to the subwavelength scale. The designed microcavity possesses a resonant mode with a quality factor of 1609 and a modal volume of 0.01 cubic wavelength. The constant period and the large structure tolerance make it realizable by current processing techniques.